2022
DOI: 10.3390/su14138120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the D&M IS Success Model in the Context of Accounting Information System and Sustainable Decision Making

Abstract: The Accounting Information System (AIS) is generally employed for the automation of operational processes and the enhancement of company efficiencies, but more recently, AIS developments have had a great effect on the process of sustainable decision-making among organizations. However, previous research on the AIS and its capabilities attributed its success to critical success factors. Therefore, in the current work, De Lone and Mc Lean’s Information System (D&M IS) Success Model is evaluated in terms of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 93 publications
1
27
0
8
Order By: Relevance
“…In addition, this method is mostly used to measure the impact of research articles and to estimate how much influence a selected research article has on future research. It usually does this by counting the number of times the article is cited after it is published (Kraus et al 2022 ; Lutfi et al 2022a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this method is mostly used to measure the impact of research articles and to estimate how much influence a selected research article has on future research. It usually does this by counting the number of times the article is cited after it is published (Kraus et al 2022 ; Lutfi et al 2022a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…Successful product innovation through big data use has been linked to innovation process acceleration, customer connections, and innovation ecosystem development (Lutfi et al 2022a , b ; Agostini et al 2019 ; Yoo et al 2012 ; Zhan et al 2017 ; Al-Gasawneh et al 2020 ; Al-Adamat et al 2020 ). Additionally, Zhan et al ( 2017 ) and Wamba et al ( 2017 ) reported that big data analytics can reduce firm cost.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies support a general significant relationship between system quality and use of IS including Almaiah et al (2022i) and Quintero et al (2009) . Also, Lutfi et al (2022g) looked into the post use of IS and found SQ to have a significant influence over it. This went the same for Xu et al (2013) , using an a3Q model, proposed, by Nelson et al (2005) , whereby the focus is placed on the, effect of SQ on the adoption of IS and was validated by findings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Sistem informasi akuntansi juga membantu dalam pemeliharaan, pemrosesan, dan penyebaran data tersebut kepada para pemangku kepentingan internal dan eksternal. Menurut (Lutfi et al, 2022), sistem informasi akuntansi mencakup kombinasi sumber daya berbasis komputer dan teknologi informasi yang terkait untuk melacak dan melaporkan kegiatan akuntansi. Dirangkum dari artikel (Alawaqleh, 2021), sistem informasi akuntansi memproses data keuangan dan non-keuangan melalui proses transformasi dengan menerima input dan menghasilkan output secara terorganisir.…”
Section: Sistem Informasi Akuntansi Dan Kinerja Pegawaiunclassified